Topical anesthetics for needle-related pain in adults and children (TOPIC): a mini-review - Le May, Sylvie; Wu, Wenjia; Francoeur, Maxime; Dodin, Philippe; Doyon-Trottier, Evelyne; Hung, Nicole; Guingo, Estelle; Vu, An Kateri; Sylfra, Annie; Lessard, Laurence; Cara-Slavich, Stephany; DeKoven, Kathryn (Frontiers in Pain Research, 2024)
Purpose Healthcare professionals (HCP) perform various needle procedures that can be distressing and painful for children and adults. Even though many strategies have been proven effective in reducing distress and pain, topical anesthetic use before needle procedures is uncommon. However, there are limited studies in the existing literature comparing specifically liposomal lidocaine and tetracaine hydrochloride topical creams. Source This systematic review analyzed studies on the use of two anesthetic creams, Liposomal Lidocaine (Maxilene®) and Tetracaine hydrochloride (Ametop™), in children and adults undergoing a needle-related procedure. Databases searched: PubMed, CINAHL, ClinicalTrials. Only randomized controlled trials (RCT) and Controlled Clinical Trials (CCT) studies were included. Cochrane Collaboration's Risk of Bias assessment tool was used. Strictly minimally invasive procedures were included to standardize different skin needle interventions. Principal findings Only one study with 60 participants was available to be included in this review. No statistically significant difference was found in the mean pain score among both interventions. The outcomes of self-reported distress during cannulation and on HCP satisfaction were not reported. However, physiological characteristics associated with stress/anxiety and on cannulation success rate were reported and did not show statistical significance. Conclusion Little to no evidence regarding the most efficient cream between liposomal lidocaine and tetracaine hydrochloride for pain management during needle-related procedures was found. Further studies, particularly RCT with larger sample sizes and standardized outcome measures, are needed to confirm the relative efficacy of either anesthetic cream.